Allometric models for estimating biomass and carbon in Alnus acuminata - Fonseca, William (2013)
In order to quantify the climate change mitigation potential of forest plantations, information on total biomass and its growth rate is required. Depending on the method used, the study of the biomass behavior can be a complex and expensive activity. The main objective of this research was to develop allometric models to estimate biomass for different tree components (leaves, branches, stem and root) and total tree biomass in Alnus acuminata (Kunth) in Costa Rica. Additionally, models were developed to estimate biomass and carbon in trees per hectare and for total plant biomass per hectare (trees + herbaceous vegetation + necromass). To construct the tree models, 41 sampling plots were evaluated in seven sites from which 47 trees with a diametric from 4.5 to 44.5 cm were selected to be harvested. In the selected models for the stem, root and total tree biomass, a r 2 >93.87 % was accomplished, while the r 2aj for leaves and branches was 88 %. For the biomass and carbon models for total trees and total plant biomass per hectare the r2 was >99 %. Average biomass expansion factor was 1.22 for aboveground and 1.43 for total biomass (when the root was included). The carbon fraction in plant biomass varied between 32.9 and 46.7 % and the percentage of soil carbon was 3 %.